Study the Effect of Educational Groups’ Activities on Knowledge and Continuous Development of Competencies and Empowerment of Professional teachers in Parsian Department of Education - Ranjbar, Mokhtar; Pasalar, Zeynab (IJRDO- Journal of Educational Research, 2017)
The main purpose of this study is to investigate the effect of educational groups’ activities on Knowledge and Continuous Development of Competencies and Empowerment of Professional teachers in Parsian department of education. This research is applied and descriptive-analytical one. The population of the study consists of 1,845 from all teachers and staffs under the supervision of Parsian Department of Education. In this research, simple random sampling was used to determine the sample. Based on the Morgan’s table and Cochran’s formula, 317 people were selected as the statistical sample. The classes of this statistical sample included 150 first-year high school students and 167 from secondary high school students. Research instruments were three researcher-made educational questionnaires, knowledge and continuous development questionnaire, and standard questionnaire for professional empowerment of teachers (Mollaeenejad, 2012). To evaluate the validity of the variables, the method of cluster analysis was used. Cronbach’s alpha was used to measure its reliability and it was 0.88. The linear and multivariate regression analysis methods were used to analyze the hypotheses test. SPSS software was used for analysis. In general, based on the test conducted and the results obtained from knowledge and continuous development of the competencies of the professional empowerment of teachers in Parsian department of education, it shows that the activities of the educational groups and their components, knowledge and continuous development have positive effects on the continuing competencies of the professional empowerment of teachers in Parsian department of education.